PENGARUH AIR SUMUR DAN AIR SABUN TERHADAP AKTIVITAS MITOSIS SEL AKAR BAWANG (Allium cepa L. - Christian Yopie Daniel Siregar Siagian; Siti Annisa Kusbama; Khory Aulia; Nazla Suhaila Parinduri; Santi Dameana Habeahan; Larasati Arum Utami; Hestia Hairima (Jurnal Biogenerasi, 2026)
Mitosis is a cell division process that plays an important role in plant growth. This study aimed to determine the effect of well water and soapy water on the mitotic activity of onion root cells (Allium cepa L.). This research used a descriptive observational method through laboratory practicum with onion roots as the research object. Data were collected through direct observation using a light microscope on mitotic phases of onion root preparations stained with acetocarmine. The results showed that well water produced better root growth and mitotic activity than soapy water. The phases of prophase, metaphase, anaphase, and telophase were more clearly observed in the well water treatment, while fewer dividing cells and damaged tissues were found in the soapy water treatment. It can be concluded that soapy water has a negative effect on the mitotic activity of onion root cells.